Iptek bagi Masyarakat untuk Melestarikan Kebudayaan Ketoprak dan Sholawat Pitutur Melalui Website Berbasis SEO Sebagai Media Informasi dan Promosi - Hayaty, Mardhiya; Laksito, Arif Dwi (JPP IPTEK (Jurnal Pengabdian dan Penerapan IPTEK), 2017)
Ketoprak and sholawat pitutur began to dim with the development of the modern era. Folk art that became the cultural root of the village community Seyegan must continue to be preserved. To preserve the efforts made through the promotion through information technology media in this case the manufacture of SEO-based art sites (Search Engine Optimazation) for the existence of this art continues to grow with the local community and can be known by the public. The process of website creation begins with several designs such as web structure, layout, features available as well as the application of SEO on some articles. Promotion of folk art through the medium of information technology is expected to revive the arts ketoprak and sholawat as well as affect the welfare of members of the arts group.